Confronting food insecurity through agricultural interventions: the Farmer FIRST program in India - Venkatesan, Purushothaman; Sivaramane, Nilakandan; Srinivasa Rao, Ch; Venkattakumar, Ramanujam; Sivakumar, Sethuraman; Mooventhan, Palanisamy; Burman, Rajarshi Roy; Kalyani, Bommu; Challa, Lalitha Navya (Frontiers in Nutrition, 2025)
IntroductionNutrition-sensitive agricultural interventions are crucial in addressing malnutrition and promoting food security. The Farmer, Farm, Innovation, Resources, Science, and Technology (FIRST) Program is a national-level agricultural intervention program that was started in 2016 by the Indian Council of Agricultural Research (ICAR). Its primary objective is to transform the lives and livelihoods of Indian farmers, with a focus on income and livelihood security. This program envisages agricultural interventions ensuring national food security goals, with improved agricultural practices, enhanced food production, and increased access to nutritious food, especially for vulnerable populations.MethodsThis study aims to investigate the food security improvement resulting from implementing nutrition-sensitive interventions introduced under the Farmer FIRST Program (FFP) in 15 agroecological zones. Four key indicators were employed to assess food security in the technology-focused field intervention: food availability, purchasing power, food gap, and food diversity. Food availability was measured at the macro level (state or national) using per capita food availability. However, at the micro level, particularly for farmers who produce their food and are secure in terms of availability, yield increases from the selected interventions under FFP served as an alternative measure. Purchasing power was assessed by the additional income generated to buy food during the off-season. The food gap was assessed using the cereal equivalent quantity (CEQ), which captures an aspect of consumers’ nutritional security. Its impact in India was evaluated using the propensity score matching technique with difference-in-difference (D-i-D) measure to estimate the unbiased overall effect on food security. Food diversity was captured using Barry’s index.ResultsA sample of 2,282 respondents were interviewed from 2016 to 2020 to elicit data on the prevalence of undernutrition in India, which is 16.3%. The results revealed that post-intervention of the FFP, cereal availability increased by 147.74% in the Northern Plain, while pulses recorded over 200% growth in three regions. The incremental per capita farm income exceeded INR 20,000 in several zones, with the Northern Plain showing an increase of over 21 times. Food diversity improved marginally, supported by the integrated farming system. Overall, FFP interventions transformed nutritional security, benefiting 1,915 households, particularly in regions with historically low calorie intake, thereby demonstrating substantial gains in food security and living standards.ConclusionThe Farmer FIRST Program (FFP) has significantly improved dietary intake among participating households, enhancing food security. Nutrition-sensitive agricultural interventions under the FFP have reduced undernutrition by increasing food availability, boosting purchasing power, and narrowing the food gap.